2006
DOI: 10.1093/ajcn/84.6.1498
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of serum ferritin concentrations as indicators of total-body iron stores in survey populations: the role of biomarkers for the acute phase response

Abstract: These analyses show that a low prevalence of inflammation has little influence on the distribution of ferritin, and 2 common indicators of inflammation do not perform equally well in identifying persons who may have elevations in ferritin due to inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
91
1
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(102 citation statements)
references
References 27 publications
6
91
1
4
Order By: Relevance
“…However, as previously mentioned in contrast to our results others have observed positive 322 relationships between inflammation markers and sTfR (10)(11)(12)(13)(14) or shown that that sTfR 323 decreased in malaria (8). In addition to increased erythropoiesis, higher sTFR concentrations 324 in children with infections may also be due to poorer iron status.…”
contrasting
confidence: 71%
See 1 more Smart Citation
“…However, as previously mentioned in contrast to our results others have observed positive 322 relationships between inflammation markers and sTfR (10)(11)(12)(13)(14) or shown that that sTfR 323 decreased in malaria (8). In addition to increased erythropoiesis, higher sTFR concentrations 324 in children with infections may also be due to poorer iron status.…”
contrasting
confidence: 71%
“…sTfR 60 is believed to be less affected by inflammation (4), although there are discrepancies in the 61 literature regarding the relationship between inflammation, infection and sTfR. Some studies 62 have shown that sTfR decreased in presence of inflammation (6,7) and malaria (8) while others 63 found higher levels of sTfR in individuals with malaria (9,10) or observed positive 64 relationships between inflammation markers and sTfR (10)(11)(12)(13)(14). It is unclear what causes these Plasmodium falciparum malaria parasite (Bioline, Malaria Ag P.f, Standard diagnostics Inc.) 124 and one drop of blood was used to estimate haemoglobin concentration using a HemoCue 125 device (HB 301, Ängelholm, Sweden).…”
mentioning
confidence: 99%
“…Probably frequent fasting habits of Jains are responsible for iron defi ciency in them. Most of the studies in literature [11,17] have employed serum ferritin as a marker to detect iron defi ciency and <15 ng/mL levels are considered diagnostic. Majority of our participants had serum ferritin values greater than 15ng/mL.…”
Section: Discussionmentioning
confidence: 99%
“…A number of biomarkers of iron status have been developed (Mei et al 2005;Beard et al 2006Beard et al , 2007Yang et al 2008;Ayoya et al 2010;Thurnham et al 2010). Of these, the hemoglobin (Hb) concentration in the blood is commonly used to estimate the prevalence of iron deficiency.…”
Section: Biomarkers For Assessing Nutritional Statusmentioning
confidence: 99%